Dietary protein source of energy levels have no major impact on growth performance, nutrient utilisation or flesh fatty acids composition of market-sized Senegalese sole - Valente, L.M.P.; Linares, F.; Villanueva, J.L.R.; Silva, J.M.G.; Espe, M.; Escorcio, C.; Pires, M.A.; Saavedra, M.J.; Borges, Pedro; Médale, Françoise; Alvarez-Blazquez, B.; Peleteiro, J.B. (Aquaculture, 2011)
International audience A growth trial was conducted to test three isonitrogenous diets (59% crude protein, dry matter basis) for Senegalese sole during the ongrowing stage. A control diet (S-15) based on a commercial diet for sole (15% crude fat, 23 kJ g−1 energy) was compared with a plant protein based diet (S-15PP) with similar energy content. This plant-based diet was supplemented with arginine, threonine, methionine and lysine to reach the levels of the S-15 diet. A low-energy diet, S-8, was formulated with the very same feed ingredients as S-15, but dietary fish oil was reduced (8% crude fat, 21 kJ g− 1). Triplicate groups of 20 fish with a mean initial body weight of 180 g were reared at 19 °C and fed the experimental diets using automatic feeders that distributed 4 meals a day, during 8 months. At the end of the experiment all groups reached commercial size (> 300 g). Dietary treatments did not affect mean final body weight. Daily growth index was generally low (0.4–0.5) and feed conversion ratio (FCR, range 2.5–2.9) did not vary significantly between treatments. Fish fed S-8 ingested fewer lipids, but its whole body or tissue lipid was equal to fish fed the S-15 and the S-15PP diets. Sole fed the S-15PP diet showed reduced plasma taurine and increased liver vacuolisation due to excess lipid storage. This diet also induced the highest Hepatosomatic index (HSI) and viscerosomatic index (VSI). Muscle, liver or skin total lipid content did not vary significantly amongst treatments. Whole body lipid content and plasma triglycerides were significantly lower in the S-15PP than in the S-15, and cholesterol showed the same trend. Protein gain (23–27 g/kg/day), whole body protein content (18–19% wet weight) and muscle protein content (19%) were not affected by the dietary treatments. Results indicate that replacement of dietary fish meal by a mixture of plant protein sources did not adversely affect growth, feed or protein utilisation of large-sized sole, but increased vacuolization and necrosis signs in ...